Students’ Perception on Teaching Strategies for English Speaking at Madrasah Aliyah Negeri 1 Kebumen - Firharmawan, Hastri; Heriyanto, Dwi (English Education and Literature Journal (E-Jou), 2023)
Teaching strategies for speaking class of English have developed rapidly through time. In Indonesia contexts where English placed as a foreign language, teachers are challenged to vary their teaching strategies in order to have interesting manageable classes. This study dealt with students’ responses on teachers’ strategies in teaching speaking. The research was conducted at Madrasah Aliyah Negeri 1 Kebumen from May to October 2022. This research belongs to a survey research design. Researcher collected quantitative, numbered data by using questionnaires; and then, statistically analyzed the data to describe trends about responses to questions. The study involved 3 teachers teaching for the speaking class at the school and 113 students joining the class. The research revealed that there were six teachers’ strategies to have been familiarly applied. They were role plays, dialogues, discussions, playing cards, picture describing, and brainstorming. It was also found that in terms of the time allocation, the subject content, and value for the future life, the students responded positively to the teaching strategies used by the teachers. Keywords: Perception, speaking, teaching strategies